A geostatistical method in GIS to estimate the amount of seabird guano accumulated on islands and headlands of Perú - Sifuentes-García Á. (2020)
The ‘guano of the islands’ in Perú is the excrement of cormorants, boobies and pelicans (guano birds), accumulated in large deposits on islands and headlands. This guano is harvested and marketed by the governmental agency AGRORURAL to meet the demands of local organic agriculture. As part of its management and commercialization plans, AGRORURAL estimates the total quantity of guano built-up on the seabird colonies using a volumetric method. The objective of this research was to propose an alternative geostatistical method that uses the volumetric data collection as baseline but incorporates the slope of the terrain and makes estimations of the total amount and distribution of guano using an interpolation grid model in a Geographic Information System (GIS). The data of the slope of the terrain, depth of guano layer, guano density and proportion guano/rock of georeferenced sampling points (taken with a hand-held GPS) on the island/headland surface were used to interpolate the quantity of guano over the entire surface using a raster kriging model, so that each cell contained an estimated quantity of guano. For this study, six guano bird colonies were visited between June 2014 and February 2018. Based on the geostatistical method, the total quantity of guano estimated varied between 10921 t on Isla Mazorca and 26142 t on Isla Guañape Sur. The GIS grid maps showed that the quantity of guano deposits was not uniformly distributed over the island/headland surface. When the guano total quantity estimates based on the geostatistical method were validated with the amount of guano harvested, the estimation error was less than 18%. This error may decrease with the use of a submetric GPS, ground-penetrating radars and augers. An accurate method of guano volume quantification is crucial for budget, logistic and marketing planning of the guano islands and headlands of Perú. © 2020, Asociacion Argentina de Ecologia. All rights reserved.